Surviving amid chaos: Israel's nuclear strategy - Beres, Louis René (Weapons of mass destruction series (Rowman & Littlefield, Inc.), 2016)
Now facing an unprecedented configuration of threats, Israel's leaders must decide whether to continue their nuclear ambiguity policy and work to develop a strategic posture with a refined nuclear strategy. This book examines Israel's evolving strategy and explains how it underscores the complexity of strategic interactions in the Middle East.